Android malware detection method based on SimHash - Bo CHEN; Yong-tao PAN; Tie-ming CHEN (Tongxin xuebao, 2017)
A new similarity detection scheme based on hierarchical SimHash algorithm was proposed.The scheme extractd contents from different aspects to represent the APK file,then used the improved SimHash to respectively represent the file.The scheme analyzed the APK file by extracting the AndroidManifest.xml file in it,the sum of the Smali code from the decompilation of dex file,instructions extracted in Smali files,Java code set,and instructions extracted in Java code files.Through the study of Voted Perceptron voting algorithm,the scheme used trust weight method,by valuating a trust weight in every layer,then combined all the result with weight in every layer as a resule of scheme,the result can be more reasonable and more convincing.